2009
DOI: 10.1007/s00264-009-0874-2
|View full text |Cite
|
Sign up to set email alerts
|

Is distal locking with IMHN necessary in every pertrochanteric fracture?

Abstract: Two groups of patients were treated for pertrochanteric fractures (AO/ASIF 31A1+A2) with an intramedullary hip nail. In the first group of 44 patients distal dynamic locking was used, and in the second group of 74 patients the nail was not distally locked. Comparison of the two groups of patients did not show any difference in terms of the period of fracture healing, radiological and functional results or frequency of complications. In the group with a distally locked nail the surgery took 40.4 minutes, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 22 publications
0
39
0
2
Order By: Relevance
“…This was not tested in this study. Skála-Rosenbaum et al did not encounter any cases of cutout of screws after osteosynthesis of pertrochanteric fractures with two head screws [26]. In our samples with additional cerclage a fracture of the medial cortex was found in 70% of the cases without varus dislocation or a cutout, because the medial buttress remained (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…This was not tested in this study. Skála-Rosenbaum et al did not encounter any cases of cutout of screws after osteosynthesis of pertrochanteric fractures with two head screws [26]. In our samples with additional cerclage a fracture of the medial cortex was found in 70% of the cases without varus dislocation or a cutout, because the medial buttress remained (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…Compression of the head fragment along the axis of the femoral neck can occur in these fractures, with rotational stability being provided via lag screws going through the intact lateral femoral cortex. In a previous study, we showed that unlocked nailing is not associated with increased complications and is actually associated with a significant reduction in operation and fluoroscopy time [14]. The authors mentioned above concur that distal locking is only indicated for unstable comminuted fractures, fractures with secondary subtrochanteric lines, and in those with wide medullary cavities.…”
Section: Discussionmentioning
confidence: 86%
“…When addressing the distal locking issue, some authors have stated that distal locking is not necessary for most pertrochanteric AO 31-A1 + 2 fractures [8,[11][12][13][14][15]; they then used their samples to confirm that unlocked nailing was safe and not associated with increased complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, intramedullary nails are designed with various distal fixation options to improve axial and rotational stability, which can also restrain the movement of distal tip of nail when a broad femoral medullary canal was encountered . Everything has two sides.…”
Section: Introductionmentioning
confidence: 99%